A report on a tektite (australite) artefact from Calperum Station in the western central River Murray region, South Australia. Issue 1 (15th July 2020) - Roberts, Amy; Morton, Catherine; Westell, Craig; Burke, Heather; Morrison, Mick; ,
Abstract: This paper reports on the recent discovery of a flaked Australian tektite (australite) artefact at Calperum Station in the western central River Murray region, South Australia. Reports of provenanced and well-contextualised australite artefacts in Australia are rare and the find reported here is the first known example on the station and its surrounds. As such, this flaked australite allows us to enhance our understanding of the distribution, size, manufacture and use of this natural glass by Aboriginal people.